Applications of blockchain technology in long-term care: use cases, potentials, and barriers - Beate Steurer; Birgit Trukeschitz; Ulrike Schneider (BMC Health Services Research)
Abstract Background Digitalization in long-term care (LTC) is being discussed as a means of easing pressures on care service delivery, optimizing care coordination and planning processes, and improving service quality. With its advanced data protection and process automation features, blockchain technology could help solve data security and privacy issues, especially for the implementation of assistive technologies. Blockchain (BC) is thus a new technology being tapped in LTC. However, little is known about the fields, scope, and experiences of BC applications in this sector. Objective This systematic review aims to provide an extensive overview of current discussions of BC technology in LTC settings. Particular attention was given to the use cases, the objectives behind applying the new technology, and barriers as well as facilitating factors for the implementation. Method According to the PRISMA methodology, we conducted a systematic literature review of academic articles and conference papers published between 2016 and 2023. The search through the Scopus database yielded 194 results, 29 of which were selected according to our inclusion and exclusion criteria. Results Research on BC technologies has taken off in LTC since 2016. Scientific interest centers around use cases for Ambient Assisted Living (AAL), care service management, and the improved integration of care ecosystems. However, most of the selected studies discuss prototypes that have neither yet been extensively evaluated nor been implemented and tested in real-world scenarios. Among the implementation barriers, technical immaturity, stakeholder cooperation, organizational change management, access to adequate IT infrastructure and end-user acceptance issues were most evident. Conclusion Future research is needed to gain insights into context-specific implementation efforts, user experiences, benefits, and pitfalls of using BC technologies in LTC settings. While many expectations are tied to BC applications, potential negative effects have received little attention in the literature. Whether BC technology can serve as a mitigator between privacy and security preservation and improved information sharing in LTC settings is an important topic for further research.